2010
DOI: 10.1111/j.1574-695x.2010.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in chronic infections – a matter of opportunity – monospecies biofilms in multispecies infections

Abstract: It has become evident that aggregation or biofilm formation is an important survival mechanism for bacteria in almost any environment. In this review, we summarize recent visualizations of bacterial aggregates in several chronic infections (chronic otitis media, cystic fibrosis, infection due to permanent tissue fillers and chronic wounds) both as to distribution (such as where in the wound bed) and organization (monospecies or multispecies microcolonies). We correlate these biofilm observations to observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
284
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 369 publications
(300 citation statements)
references
References 87 publications
7
284
0
5
Order By: Relevance
“…Second, the defect in biofilm formation was another in vitro phenotype exhibited by the purL mutant (Figure 2c). Bacterial biofilm formation is one of the adaptation mechanisms to various environments and has been reported to be required for chronic infections and symbioses (Costerton et al, 2003;Ramey et al, 2004;Visick, 2009;An and Grewal, 2010;Burmølle et al, 2010;Morris and Visick, 2010;Rinaudi and Giordano, 2010;Maltz et al, 2012). In squid-Vibrio symbiosis, Vibrio fischeri uses a transient biofilm to colonize its host, Euprymna scolope (Visick, 2009;Morris and Visick, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the defect in biofilm formation was another in vitro phenotype exhibited by the purL mutant (Figure 2c). Bacterial biofilm formation is one of the adaptation mechanisms to various environments and has been reported to be required for chronic infections and symbioses (Costerton et al, 2003;Ramey et al, 2004;Visick, 2009;An and Grewal, 2010;Burmølle et al, 2010;Morris and Visick, 2010;Rinaudi and Giordano, 2010;Maltz et al, 2012). In squid-Vibrio symbiosis, Vibrio fischeri uses a transient biofilm to colonize its host, Euprymna scolope (Visick, 2009;Morris and Visick, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2) and this might explain how the bacteria survive inside the wound bed. In chronic wounds individual micro colonies might exist that only consist of single species, and it is very likely that mono-and polymicrobial biofilms can be found in the same ulcer, but the importance and relevance of this has yet to be established (Kirketerp-Moller et al, 2008;Burmølle et al, 2010). There are also biofilms in healing wounds, and other factors like host response, virulence and antibiotic resistance seem important for the fate of the wound.…”
Section: Microbial Diversitymentioning
confidence: 99%
“…Chronic wounds infecting bacteria are generally present in biofilm form 32 .Therefore pharmaceutical products with biofilm disrupting activity are extremely necessary for chronic wound treatment. It was demonstrated that the biofilm disruption showed by LAPS 7,8 is due to synergism between surfactants (Tween 80, 1-mono-linolein, 1,2-dipalmitin and distearin) 8,33 , an extracellular DNAase 8,19 and variations in the ionic strength (Na, K and Mg salts) 8,34 .…”
Section: Supernatants Biofilm Disruption Activitymentioning
confidence: 99%